Dárdai Zsuzsa Elektroaurák c. kiállításának megnyitója
Zsuzsa Dárdai is a member of Árnyékkötők art group. Her electro-graphics exhibition in Vasas Mini Gallery is opened by photography historian Gábor Szilágyi.